2018
DOI: 10.5582/bst.2018.01009
|View full text |Cite
|
Sign up to set email alerts
|

Renal protective effect of Paeoniflorin by inhibition of JAK2/STAT3 signaling pathway in diabetic mice

Abstract: Paeoniflorin is the main bioactive components of the root of P.lactiflora Pall., and has been widely used as an anti-inflammation and immunomodulatory agent. However, the effect and mechanisms of Paeoniflorin in diabetic nephropathy (DN) remains to be elucidated. In the present study, streptozotocin (STZ)-induced type 1 diabetic mice model was used to investigate the protective effect of Paeoniflorin and the role of the Janus kinase (JAK) 2/signal transducer (STAT) 3 signaling pathway on DN. After treatment wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…LPS induces the activation of retinal astrocytes via the JAK2/STAT3 signaling pathway ( Jang et al 2007 ). The JAK2/STAT3 signaling pathway also contributes to the development of diabetic macrovascular complications by mediating inflammation associated with vascular endothelial cells and/or monocytes ( Yang et al 2017 ) and involves the renal protective effect of paeoniflorin ( Li et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…LPS induces the activation of retinal astrocytes via the JAK2/STAT3 signaling pathway ( Jang et al 2007 ). The JAK2/STAT3 signaling pathway also contributes to the development of diabetic macrovascular complications by mediating inflammation associated with vascular endothelial cells and/or monocytes ( Yang et al 2017 ) and involves the renal protective effect of paeoniflorin ( Li et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniflorin, a monoterpene glucoside, is the main active ingredient of the root of P. lactiflora and has multiple biological activities such as antioxidation, cognition-enhancing, anticoagulation, anticonvulsant, vasodilation, mild sedation, and potent analgesia [39, 40]. Till now, the protective roles of PF refer to amelioration of DM or its complications, such as diabetic nephropathy [21, 41], and cardiovascular events [19], nothing about PF and hyperglycemia fluctuation. In this study, it demonstrated that PF could alleviate vascular injuries induced by hyperglycemia fluctuations in terms of the release of TNF- α , PECAM-1, oxidative stress, and the expression of PKC β 1 in HUVECs subjected to intermittent glucose levels and in DM rats with fluctuating hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Paeoniflorin (PF, Figure 1) is an important component of Paeonia lactiflora Pall that shows various protective effects on the cardio-cerebral vascular system, mediated by antiapoptosis [16], anti-inflammation [17], and antioxidantation [18]. Furthermore, PF is reported to play an essential protective role in both DM-associated macrovascular complications, such as myocardial infarction via the transient receptor potential vanilloid 1/calcitonin gene-related peptide pathway [19], and DM-associated microvascular complications, such as diabetic nephropathy with renal protective effects by prevention of TLR2/4-mediated inflammation [20] or inhibition of the JAK2/STAT3 signaling pathway [21]. However, the effects and mechanisms of PF on glucose fluctuation-induced damages remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate, based on these observations, that PF can improve the inflammatory status in DN through inhibiting the TLR4 pathway. Moreover, the anti-inflammatory mechanism of PF is also associated with other signaling pathways (Shao et al, 2016; Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%